Strong varieties are the basis to produce high-quality processing products of bread wheat grain - I. V. Pakhotina; E. Yu. Ignatieva; I. A. Belan; L. P. Rosseeva; L. T. Soldatova (Зерновое хозяйство России)
There have been studied new strong varieties of spring bread wheat of different maturity groups (‘Tarskaya 12’, ‘Omskaya 44’ and ‘Omskaya 42’) in comparison with the standards (‘Pamyati Azieva’, ‘Duet’ and ‘Element 22’) and foreign varieties in the conditions of the south of Western Siberia. The purpose of the study was to identify the advantage of the studied wheat varieties recommended for cultivation in the Omsk region to produce grain with high baking properties. The study was carried out based on the selection crop rotation of the laboratory for spring bread wheat breeding in the nursery of Competitive Variety Testing, as well as the department of seed production when sown on fallow (intense background) in the zone of the southern forest-steppe of the Omsk region of the FSBSI “Omsk ARC”. There has been conducted a bakery quality estimation and qualification of samples according to the methodologies and classification standards recommended by the State Commission for Variety Testing of Agricultural Plants. There was identified an advantage of the medium-early variety ‘Tarskaya 12’ according to the formation of gluten amount in grain (+3.2...4.2 %), dough dilution (–34...50 u.f.), dough resilience (+24...43 mm) and flour strength (+113...188 u); middle maturing variety ‘Omskaya 44’ on the formation of dough resilience, flour strength in comparison with the standards. The middle-late variety ‘Omskaya 42’ was distinguished by high baking characteristics in comparison with the standard ‘Element 22’. A comparative analysis of the technological properties of new varieties and foreign breeding has revealed the advantage of the studied domestic varieties in formation of protein in grain and flour strength.